Enhancing food security through increased labor productivity of AIC workers - Saginova, S.A. (BUKETOV BUSINESS REVIEW, 2018)
The article presents the challenges of AIC development in the regions of the Republic of Kazakhstan based on the growth in labor productivity of workers in the agrarian sector, which will raise competitiveness of the agrarian enterprises and enhance the country`s food security. Joining the ranks of the most developed countries necessitates development of regions through new technologies involved. The article notes a significant decrease in the population employed in agriculture, forestry and fisheries, the continuing migration from rural areas to cities, which causes a decline in agricultural production. Increasingly urgent is to develop agrarian entrepreneurship, so the priority task is the growth of labor productivity. The author mentions as an example the foreign experience of the developed countries of Germany, France, etc. EAEU membership ensures free migration of labor within the states of this commonwealth, which allows individual countries to reduce unemployment and achieve GDP growth. The study emphasizes the need to increase the role of knowledgebased, resource-saving technologies and industries, as evidenced in the message to the people of Kazakhstan by the President N.Nazarbayev «New Opportunities for Development in the context of the Fourth Industrial Revolution». In Kazakhstan, the material and technical base of agriculture is characterized by diversity due to its diversified structure, since each of the AIC branches is characterized by a different ratio of basic and circulating assets, especially in such sectors as harvesting, storage and processing of agricultural products. It is therefore necessary to raise the innovation and technological level of developing AIC sectors and sub-sectors by introducing new technologies and equipment, and improving the skills of rural workers through an effective investment policy, state support, agricultural cooperatives, which should unite the efforts of peasant farms, private subsidiary farms, etc.